Assessment of Records Management in Registry Department of Kebbi State University of Science and Technology - Gautam, Madhuri; Verma, Maya (International Journal of Information Studies, 2025)
Records are a vital asset in ensuring that the institution is governed effectively and efficiently, and is accountable to its staff, students and the community that it serves. The major purpose of this study was to assess record management of the registry department of Kebbistate University of science and technology Aliero. To be able to achieve this objective, research questions were formulated and answers obtained, which centered on records creation, record management policy, challenges facing records management. There view of related literature revealed that there is need for records to be properly managed and in doing so there is need for good records management policy that clearly spells out the various programs required for effective records management. Survey research method was used involving questionnaire, and observation. The findings revealed that the registry department of the University still has a long way to go with respect today records management. The study recommended provision for adequate, modern, safe and functional storage facilities, sufficient and regular funding, recruitment of trained personnel, on the job training for existing staff, computerization of all units records, and uninterrupted power supply to all parts of the unit as a means of ensuring proper records management.